2021
DOI: 10.1002/jmv.26836
|View full text |Cite
|
Sign up to set email alerts
|

Gastroenterology manifestations and COVID‐19 outcomes: A meta‐analysis of 25,252 cohorts among the first and second waves

Abstract: A meta-analysis was performed to identify patients with coronavirus disease 2019 presenting with gastrointestinal (GI) symptoms during the first and second pandemic waves and investigate their association with the disease outcomes. A systematic search in PubMed, Scopus, Web of Science, ScienceDirect, and EMBASE was performed up to July 25, 2020. The pooled prevalence of the GI presentations was estimated using the random-effects model. Pairwise comparison for the outcomes was performed according to the GI man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 157 publications
(274 reference statements)
2
39
0
11
Order By: Relevance
“…Although acute respiratory system dysfunction is the primary symptom of COVID-19, the presence of digestive system disruptions in COVID-19 is increasingly recognized [ 64 ]. Moreover, a recent meta-analysis of patients with COVID-19 presenting with gastrointestinal symptoms on admission showed a higher risk of respiratory, cardiac, and renal complications, including increased mortality [ 65 ]. Women with PCOS have an increased risk of other gastrointestinal issues including irritable bowel syndrome [ 66 , 67 ], which may itself portend a higher risk of infection [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although acute respiratory system dysfunction is the primary symptom of COVID-19, the presence of digestive system disruptions in COVID-19 is increasingly recognized [ 64 ]. Moreover, a recent meta-analysis of patients with COVID-19 presenting with gastrointestinal symptoms on admission showed a higher risk of respiratory, cardiac, and renal complications, including increased mortality [ 65 ]. Women with PCOS have an increased risk of other gastrointestinal issues including irritable bowel syndrome [ 66 , 67 ], which may itself portend a higher risk of infection [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gastrointestinal symptoms have been also associated with reduced number of circulating lymphocytes, and the circulating lymphocytes were inversely associated with virus discharge in stool (58). Moreover, a recent meta-analysis on gastrointestinal symptoms of SARS-CoV-2 infection concluded that gastrointestinal symptoms on admission were associated more with complications, including ARDS, acute cardiac injury, and acute kidney injury (57).…”
Section: Composition Of the Gut-lung Microbiota In Cases Of Severe Covid-19 Pneumoniamentioning
confidence: 99%
“…Наиболее распространенными были анорексия (19,9%), дисгевзия / агевзия (15,4%), диарея (13,2%), тошнота (10,3%) и гематомезис (9,1%). Около 26,7% пациентов подтвердили положительную фекальную РНК с постоянным выделением вируса в среднем в течение 19,2 дней [11].…”
Section: код мкбunclassified
“…Бутлерова, 49 10 Федеральное государственное бюджетное образовательное учреждение высшего образования «Чувашский государственный университет им. И. Н. Ульянова», 428015, Россия, г. Чебоксары, Московский проспект, 45 11 Бюджетное учреждение высшего образования ХМАО-Югры «Сургутский государственный университет», 628412, Россия, Ханты-Мансийский автономный Округ-Югра, г. Сургут, пр. Ленина, 1 12 Федеральный исследовательский центр «Информатика и управление» Российской академии наук, 119333, Москва, ул.…”
unclassified